1995
DOI: 10.1177/019874299502000302
|View full text |Cite
|
Sign up to set email alerts
|

Time Estimation and Planning Abilities: Students with and without Mild Disabilities

Abstract: In this study we sought to examine differences among groups of elementary students with and without disabilities on a measure of time estimation. We assessed the time estimation recall of 51 students with and without emotional handicaps, learning disabilities, and attentional disorders and examined the relationship between time estimation and the self-regulatory skills of planning and organization. Group differences in time estimation recall were documented, but these differences were no longer significant aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…• Children with ADHD struggle in planning activities within a time framework. These time-estimation skills are needed in the classroom to arrive on time, complete tasks within defined limits, and monitor test taking (Grskovic, Zentall, & Stormont-Spurgin, 1995). Research indicates serious deficiencies in these abilities for ADHD populations.…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Children with ADHD struggle in planning activities within a time framework. These time-estimation skills are needed in the classroom to arrive on time, complete tasks within defined limits, and monitor test taking (Grskovic, Zentall, & Stormont-Spurgin, 1995). Research indicates serious deficiencies in these abilities for ADHD populations.…”
Section: Characteristicsmentioning
confidence: 99%
“…Research indicates serious deficiencies in these abilities for ADHD populations. In particular, individuals with attention disorders tend to overestimate the length of time intervals (Grskovic et al, 1995;Turnbull et al, 1999), posing serious implications for classroom performance, including procrastination and failure to complete tests and assignments. • Children with ADHD often have poor handwriting-often, haphazard and illegible.…”
Section: Characteristicsmentioning
confidence: 99%
“…Previous studies demonstrated that children with an impulsive responding style, similar to that seen in ADHD, performed more poorly on questionnaires regarding time concept abilities (Goldman & Everett, 1985;Grskovec, Zentall, & Stormont-Spurgin, 1995) and on time reproduction tasks (Walker, 1982). Children with ADHD have also been shown to have impairments on administered time estimation tasks.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that children with ADHD are more affected than controls but only under low-arousal conditions (Shaw & Brown, 1999). A second study found that students with elevated symptoms of ADHD estimated that their daily activities took less time than did those without ADHD but not after controlling for IQ (Grskovic, Zentall, & Stormont-Spurgin, 1995). A third study found differences between children defined as "impulsive" and controls, but there was no evidence that the participants actually had diagnosed ADHD (Goldman & Everett, 1985).…”
mentioning
confidence: 99%